(untitled) (International Journal of Pharmaceutical Sciences and Drug Research, 2012)
Cardiac hypertrophy has been considered as an important risk factor for cardiac morbidity and mortality whose prevalence has increased during the last few decades. Cardiac hypertrophy, a disease associated with the myocardium, is characterized by thickening of ventricle wall of heart and consequent reduction in the contracting ability of heart to pump the blood. Cardiac hypertrophy has been divided into two types, i.e. physiological and pathological hypertrophy. The exercise-induced increase in the ability of pumping blood leads to thickening of ventricle wall, referred to as physiological hypertrophy. On the other hand, reduced ability of pumping blood as a result of hypertension and volume overload on heart denotes pathological hypertrophy. Numerous mediators have been found to be involved in the pathogenesis of cardiac hypertrophy that include mitogen-activated protein kinase (MAPK), protein kinase C (PKC) insulin-like growth factor-I (IGF-I), phosphatidylinositol 3-kinase (PI3K)-AKT/PKB, calcinurin-nuclear factor of activated T cells (NFAT) and mammalian target of rapamycin (mTOR). The prevention strategy for cardiac hypertrophy involve thiazide diuretics, angiotensin-converting enzyme (ACE) inhibitors, angiotensin (Ang) II receptor blockers, beta blockers and calcium channel blockers. The present review article highlights the signaling mechanisms involved and the approaches required in the treatment of cardiac hypertrophy.